Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Pemahaman Konsep Bilangan Pecahan Siswa Kelas VII Sekolah Menengah Pertama - Ramadan Kristian Novianto; Ubaidillah Aisy Kodir; Finufal Ahmad Faurudi; Nur Wiji Sholikin (IEC: Journal of Educational Innovation, 2026)
Fractions are one of the mathematics topics that most frequently pose obstacles for seventh-grade junior high school students, largely because instruction remains teacher-centered, leaving students passive and without the opportunity to construct their own understanding. This study aims to determine the effect of implementing the Problem Based Learning (PBL) model on improving students' conceptual understanding of fractions in class VII at SMP NU Bantaran. This research employed a quantitative approach with a pre-test post-test design, involving 28 students selected through purposive sampling technique, using a written test instrument developed based on ten indicators of conceptual understanding of fractions and validated prior to use. Learning was implemented through five systematic PBL stages, and the data were analyzed using descriptive statistics and the nonparametric Mann-Whitney test, as the data were not normally distributed. The results showed a significant increase in the mean score, from 27.32 in the pre-test to 62.85 in the post-test, with the Mann-Whitney test yielding a significance value of 0.000, which is smaller than the 0.05 significance level, so H0 was rejected and H1 was accepted, indicating a significant difference in student learning outcomes before and after the implementation of the Problem Based Learning (PBL) model.